An Appraisal of Health Care Facilities: A Case Study of Sewaprui Block (Varanasi District) - Ratawa, Meeta; Sharma, P.R. (National Geographical Journal of India, 2022)
The quality of life is considered as one of the fundamental rights of human being. Therefore good health is a prime and vital indicator of the quality of life. It becomes an earnest need to provide health care facilities and services to all its citizens especially in rural areas. As a geographer, it is needed to study the spatial organization of the settlement systems and to provide the network of health centres. The Rural Health care delivery system in India comprises the hierarchy of the Community Health Centres (CHCs), Primary Health Centres (PHCs) and Sub Centres (SCS) to provide curative and specialized health facilities to rural population. The present study attempts to describe the present spatial pattern and efficiency of rural health care delivery system in Sewapuri block an locations of additional health care facilities within the block. The accessibility to the health care facilities remains a problem here. Growing population and growing expectations of the people along with the rising costs of health care have produced a challenge for transforming the public health care into an accountable, accessible and affordable system of quality services.